2019
DOI: 10.1021/acs.inorgchem.9b02062
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Zn–Zn and Zn–Pd Bonded Complexes by Reactions of Terminal Zinc Hydrides with Pd(II) Species

Abstract: Divalent palladium-induced homocoupling of terminal zinc hydrides to zinc−zinc bonded complexes was achieved herein. Reactions of zinc hydrides [LZnH] (L = CH 3 C(2,6-i Pr 2 C 6 H 3 N)CHC(CH 3 )(N(CH 2 ) n CH 2 PPh 2 ); 1a: n = 1; 1b: n = 2) with 0.5 equiv of allyl(cyclopentadienyl)palladium(II) afforded heterotrinuclear [Zn 2 Pd] complexes 3 containing direct Zn−Zn and Zn−Pd bonds, with concomitant elimination of propylene and cyclopentadiene. Complexes 3 were also accessed by the reactions of zinc hydrides 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The chemistry of zinc complexes has undergone a remarkable renaissance in the past decade. The renewed interest toward these compounds has mainly arisen from their attractive reactivities and potential applications in a broad range of reactions, including the hydroboration of alkynes, , the Strecker reaction, the Barbier reaction, the aminophenol oxidation reaction, the C–S cross-coupling reaction, the hydrosilylation of N-heterocycles, the copolymerization of epoxides and CO 2 , and so forth. , Zinc is an inexpensive, biocompatible, less toxic and earth-abundant metal, which makes it particularly appealing to replace toxic and/or noble-metal complexes in catalytic transformations. Thus, the synthesis of zinc complexes with high catalytic activity is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of zinc complexes has undergone a remarkable renaissance in the past decade. The renewed interest toward these compounds has mainly arisen from their attractive reactivities and potential applications in a broad range of reactions, including the hydroboration of alkynes, , the Strecker reaction, the Barbier reaction, the aminophenol oxidation reaction, the C–S cross-coupling reaction, the hydrosilylation of N-heterocycles, the copolymerization of epoxides and CO 2 , and so forth. , Zinc is an inexpensive, biocompatible, less toxic and earth-abundant metal, which makes it particularly appealing to replace toxic and/or noble-metal complexes in catalytic transformations. Thus, the synthesis of zinc complexes with high catalytic activity is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we designed and synthesized a new type of tridentate β-diketiminato ligand with a pendent phosphine group [CH 3 C­(2,6- i Pr 2 C 6 H 3 N)­CHC­(CH 3 )­(NCH 2 CH 2 PPh 2 )], which could stabilize a series of highly reactive rare-earth metal complexes . Remarkably, treatment of NNP ligand-based zinc hydrides with a palladium-based TM complex resulted in dehydrocoupling to afford a η 2 -dizinc-bonded complex of palladium . We proposed that such a tridentate NNP ligand plays a critical role in the formation of the metal–metal bonded complex.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we found that a palladium( ii ) reagent, allyl(cyclopentadienyl)-palladium, also enabled the formation of the [Zn 2 Pd] complex 39b from zinc hydride 38b (Scheme 12). 36 Mechanistic studies revealed that the Zn–Pd bonded complex 41 was initially generated by the elimination of propylene, which could be transformed into 39b by further reaction with one molar equivalent of zinc hydride with the release of cyclopentadiene.…”
Section: Synthesis Of Heterometallic Complexes Containing Mg- or Zn-m...mentioning
confidence: 99%
“…On the other hand, cooperative activation of Lewis acidic metalloligands and transition metals was also mentioned. 27,30,36,37 To date, the stoichiometric reactions of heterometallic complexes with a variety of small molecules have been extensively studied and they exhibit versatile reactivities. In contrast, catalytic reactions based on Mg/Zn-based heterometallic complexes are far less developed.…”
Section: Reactivities Of Heterometallic Complexes Containing Mg- or Z...mentioning
confidence: 99%
See 1 more Smart Citation